Soliton-Effect Optical Pulse Compression in Bulk Media with X^(3) Nonlinearity - Tamošauskas, G.; Dubietis, A.; Valiulis, G. (Nonlinear Analysis: Modelling and Control, 2000)
Self-compression of visible optical pulse in bulk χ(3) medium has been demonstrated taking the advantage of negative group-velocity dispersion of tilted pulses.
Keywords: temporal solitons; tilted pulses; self-phase-modulation; pulse compression